EEMCRP: Energy Efficient Multi-hop Clustering Routing Protocol for Wireless Sensor Networks - Samra BOULFEKHAR; Fatima BELAMRI; Mohammed BENMOHAMMED; Djamil Aïssani (Journal of Digital Information Management, 2022)
Clustering is the key to overcoming the energy challenge in the wireless sensor network. For this reason, we propose a novel static clustering routing protocol called Energy Efficient Multi-hop Clustering Routing Protocol for Wireless Sensor Networks (EEMCRP). EEMCRP, partitions the network into static clusters, eliminates the overhead of dynamic clustering and distributes the energy load among high power sensor nodes by using Secondary-cluster-heads. EEMCRP partitions the nodes into unequal size clusters. Clusters closer to the base station have smaller sizes than those farther away from the base station. Thus, cluster heads closer to the base station can preserve some energy for the inter-cluster data forwarding. We, also, propose an energy-aware multihop routing protocol for inter-cluster communication based on Energy-Efficient Routing Protocol for wireless sensor networks (EERP). Simulation results show that our protocol balances the energy consumption well among all sensor nodes and achieves an obvious improvement on the network lifetime.